2003
DOI: 10.1093/jurban/jtg081
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation of HIV Prevention for Adolescent Females in the United States: Linking Behavioral and Epidemiologic Sciences to Reduce Incidence of HIV

Abstract: Given the increasing numbers of new HIV infections among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…HIV/STI prevention interventions, drug abuse treatment programs, and psychological counseling services are warranted (Clements et al, 2001;Nemoto et al, 2004). Targeted services for high-risk social networks can provide an opportunity to prioritize entire networks rather than just individuals for change (Centers for Disease Control and Prevention, 2005;Ellen, 2003;Guenther-Grey, Noroian, Fonseka, & Higgins, 1996). In addition to previous recommendations to tailor services and interventions to be both culturally and linguistically appropriate for transgender women and their partners (Blaza, 2004;Scheer et al, 2004), it is imperative to provide interventions at a macrolevel or ''upstream'' (referring to a common public health metaphor) that address structural challenges and environmental influences on well-being and health outcomes at the source.…”
Section: Discussionmentioning
confidence: 99%
“…HIV/STI prevention interventions, drug abuse treatment programs, and psychological counseling services are warranted (Clements et al, 2001;Nemoto et al, 2004). Targeted services for high-risk social networks can provide an opportunity to prioritize entire networks rather than just individuals for change (Centers for Disease Control and Prevention, 2005;Ellen, 2003;Guenther-Grey, Noroian, Fonseka, & Higgins, 1996). In addition to previous recommendations to tailor services and interventions to be both culturally and linguistically appropriate for transgender women and their partners (Blaza, 2004;Scheer et al, 2004), it is imperative to provide interventions at a macrolevel or ''upstream'' (referring to a common public health metaphor) that address structural challenges and environmental influences on well-being and health outcomes at the source.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship held true across similar grades of CIN. Furthermore, African American women were more likely to be coinfected with multiple types of HPV compared to European American women for unclear reasons [79,81,82,83]. Other studies have also demonstrated that black, Hispanic and Asian women are less likely to be infected by HPV16 or 18 compared to white women [84], whereas HPV58 and 45 are more commonly found in Hispanics than Whites [85].…”
Section: Hpv Infectionmentioning
confidence: 99%
“…Findings, however, are mixed, with some studies reporting positive associations (4), inverse associations (5), or no associations (2, 6) between acculturation and cancer screening, depending on the type of screening test or acculturation measure used. Regardless of country of origin or acculturation, Hispanics are more likely to obtain recommended cancer screenings if they have health insurance and a regular source of health care (1, 3, 4, 7). …”
Section: Overall Summary Of Cancer Statistics In Hispanicsmentioning
confidence: 99%